Utilization of Waste Plastic through the Collage Method in Elementary Schools in Jiput Village, Jiput Sub-district, Pandeglang Regency - Juanto, Ade; Syifa, Fany; Putri, Siti Septiani; Rivaldo, Ahmad; Alfiansyah; Arianna; Aji, Bayu; Maulana, Eji; Wahyudi, Ficky; Jalis; Robi; Insiyah, Siti Amanatun; Umiroh; Hayat, Zahrotul; Fanani, Khairul; Mulyawan, Galuh (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study investigates how the collage method can foster creativity and environmental awareness among elementary students in Jiput Village by utilizing plastic waste—a persistent environmental issue. Method: Using a qualitative, participatory approach, students engaged in collecting, cleaning, and repurpose plastic waste into collage art. Data was gathered through observation and documentation of student work. Practical Application: The activity reduced plastic waste in schools and enhanced students' creativity, fine motor skills, and environmental consciousness. This method can be applied in other schools as a practical environmental education tool. Conclusion: The collage method effectively promotes creativity and early environmental awareness while offering a sustainable approach to managing plastic waste in educational settings.